On the Course of Neurocutaneous Syndrome (NCS) and Its Pseudo-Diagnosis by Medical Professionals - Amin, Omar M. (Morgellon’s Disease and Neurocutaneous Syndrome (NCS): Cases and Recovery, 2021)
Neurocutaneous Syndrome (NCS) is a dental toxicity disorder causing various neurological and dermatological symptoms that are often confused by the lay patient as parasitological infections. The cases of 24 randomly selected patients determined to be NCS cases at Parasitology Center, Inc. (PCI) by OMA are presented. Previously reported and additional toxic sealants are reported. The dermatological and neurological symptoms characteristic of NCS were common to all 24 cases. Incubation period varied between a few hours and 19 years. Inaccurate interpretation of NCS symptoms by health care professionals is discussed. Faulty diagnosis undermines the patients physical and mental health and further traumatizes their quality of life especially when they are diagnosed with mental disorders and forced to submit to psychological treatment against their will. Medical professionals need to become more aware of NCS symptoms to properly tend to their patients well being.